THE IMPACT OF PHYSICAL EXERCISE ON THE SKELETAL MUSCLE CLOCK GENES (Kinesiology, 2018)
The most important circadian synchronizer is the central clock located in the suprachiasmatic nucleus (SCN) of the hypothalamus. The rhythmicity of all organs is achieved by molecular clock gene expression in the central clock and the pace is reached through neuronal and humoral signals to peripheral tissues. Skeletal muscle is one of the peripheral organs that express clock and clock controlled genes (CCGs) which display circadian rhythmicity. Recent studies have pointed out the role of clock genes in skeletal muscle function and metabolism. The expression of clock genes in skeletal muscle might be altered by several external stimuli and also by different diseases. Physical exercise is a nonphotic stimulus that can realign the skeletal muscle circadian system to the central clock, imposing a new rhythm at the organism level. This effect may be crucial to prevent or ameliorate diseases and disorders caused by disruptions of circadian rhythms. In this review, we discuss the role of clock genes in skeletal muscle function and the importance of physical exercise as a potent synchronizing stimulus for the skeletal muscle molecular clock.Key words: clock genes, physical exercise, skeletal muscle